The use of reduced copper metal–organic frameworks to facilitate CuAAC click chemistry. Issue 82 (26th September 2016) - Fu, Q.; Xie, K.; Tan, S.; Ren, J. M.; Zhao, Q.; Webley, P. A.; Qiao, G. G.
Abstract : A reduced copper metal–organic framework (rCu-MOF) containing Cu I ions was prepared and employed as a catalyst for 'Click' reactions. The rCu-MOF presents higher catalytic activity, good structural stability as well as facile recyclability compared to traditional copper halide catalysts. Abstract : A reduced copper metal–organic framework (rCu-MOF) containing Cu I ions was prepared by reducing raw MOFs (Cu-BTC). A series of polymer functionalizations and coupling reactions could subsequently be achieved via CuAAC click chemistry, thus demonstrating the high activity, facile recyclability and good structural stability of rCu-MOFs for catalytic applications.